STUDI TENTANG PEMANFAATAN E-PROCUREMENT PADA DINAS PEKERJAAN UMUM KABUPATEN KUTAI TIMUR - Muhammad Muhammad; Achmad Djumlani; Enos Paselle (Jurnal Paradigma (JP), 2019)
This study aims to determine and analyze the use of E-Procurement at the Public Works Office of East Kutai RegencyThis research is a descriptive study with a qualitative approach. Data were obtained through interviews, observation and literature review, and analyzed by interactive models. The results showed that in general, the use of E-Procurement at the Public Works Office of East Kutai Regency could facilitate the selection of auction/tender service providers because it was done through electronic websites and the internet so as to save time and costs in the auction process for the procurement of goods and services. Keywords: Utilization, E-Procurement, Procurement, Electronics, Internet.